2017
DOI: 10.37358/mp.17.1.4803
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Markers Predicting the Risk of Gestational Diabetes Mellitus

Abstract: Gestational diabetes mellitus (GDM), defined by the occurrence or discovery of glucose intolerance during pregnancy is associated with higher risk of perinatal complications and long-term development of chronic diseases both in the mother and her child. Recent data suggest that women diagnosed earlier in pregnancy, even having more risk factors, develop fewer complications. The aim of the current study is to analyse biochemical markers that play a role in the pathophysiology of GDM and could lead to an early d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Referring to patient-responsiveness, in a study published in 2018 that followed the 'skin test' response to muscle relaxants, it was found that 87% of the subjects who tested positive for this test were female, the most allergenic one being succinylcholine (35,36). This study is in agreement with the results of our research, according to which a greater predisposition of the female to develop allergic reactions post-administration of muscle relaxants (37)(38)(39).…”
Section: Discussionsupporting
confidence: 88%
“…Referring to patient-responsiveness, in a study published in 2018 that followed the 'skin test' response to muscle relaxants, it was found that 87% of the subjects who tested positive for this test were female, the most allergenic one being succinylcholine (35,36). This study is in agreement with the results of our research, according to which a greater predisposition of the female to develop allergic reactions post-administration of muscle relaxants (37)(38)(39).…”
Section: Discussionsupporting
confidence: 88%
“…Coronary disease was finding in 9.14% of CC cases. Two CC patients were pregnant at the time of diagnosis ( 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…Sevoflurane has a good safety profile pre-and intraoperatively but the delirium awakening disturb the child, the parents and recovery staff [21,22]. Pediatric patients are inconsolable in the recovery room.…”
Section: Resultsmentioning
confidence: 99%